Packets flow watermarking method based on the inter-packet delay with smooth crossed grouping - Hua JIN; Hui ZHU; Chang-da WANG (Tongxin xuebao)
To improve the self-correction ability and resist the entropy-based detection,a flow watermarking approach based on the inter-packets delays with smooth crossed grouping was proposed.Such an approach extended the watermarking methods using both the convolutional code and the smooth group methods to embed the watermarks into packet flows.By adjusting the inter-packets delays of the crossed packets,the transmission time distribution of the watermarked packets can indefinitely approach to that of any normal packets transmission times.Furthermore,the approach can mitigate the negative consequences introduced by packets transmission jitters,packets losses,packets aggregations and packets divisions for the watermarks detection.Both theoretical analysis and experimental results show that the proposed approach overweight the known watermarking methods from the aspects of identification accuracy,robustness and hiddenness.